THE METAPHOR OF ACEH LANGUAGE ON INSTAGRAM SOCIAL MEDIA: POTENTIAL AND THREATS OF HATE SPEECH IN THE PUBLIC SPACE - Mursyidin Mursyidin; Rahmad Nuthihar; Riza Hasan; RN Herman; Azrul Rizki; Wahdaniah Wahdaniah (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This research examines the using metaphors in the commentary column on Instagram social media accounts @serambinews and @haba_acehbarat. The chosen topic of metaphors due to the majority of hate speech on social media has found metaphor. As a result, victims feel aggrieved by posting social media reports to the police to be proven in court. The data collected is comments of the Instagram user in January-April 2021. From 1,750 commentary has observed are 107 metaphors consist of 51 structural metaphors, 27 orientational metaphors, and 29 ontological metaphors. The structural metaphors found in this study mostly use the term animal as a metaphorical element is almost the same as the ontological metaphor uses abstract terms to become concrete. Besides that, the orientational metaphors used for related to spatial orientation. Regards the potential for hate speech of the 1,750 comments has observed, 27 comments had the potential to be hate speech. The hate speech found in Instagram comments is defamation, insult, and provocation.